Genetic architecture and candidate gene identification for grain size in bread wheat by GWAS - Yu, Haitao; Hao, Yongchao; Li, Mengyao; Dong, Luhao; Che, Naixiu; Wang, Lijie; Song, Shun; Liu, Yanan; Kong, Lingrang; Shi, Shubing (Frontiers in Plant Science, 2022)
Grain size is a key yield trait in bread wheat breeding, and also is the most frequently selected trait during domestication. After the phenotypic characterization of 768 bread wheat accessions in three-plots for at least two years, the present study suggested that improved variety had greater grain size but lower grain protein content than these in landrace of bread wheat with significance. Using 55K SNP assay genotyping and large scale phenotyping data of the population and GWAS, we identified 5, 6, 6, and 6 QTLs for grain length, grain weight, grain area, and thousand grain weight, respectively. Seven of the 23 QTLs showed common association within different locations or years. The most significant finding of this study is the key locus for grain length, qGL-2D, which shows the highest association signals after years of multi-plot testing. Haplotype and evolution analysis indicated the superior allele of qGL-2D was mainly hidden in improved variety rather than landrace, which may be responsible for the significant grain length difference between improved variety and landrace of bread wheat. A comprehensive analysis of transcriptome and homolog showed that TraesCS2D02G414800 could be the real QTL gene for qGL-2D. Overall, this study presents several reliable grain size QTLs and candidate gene for grain length for future bread wheat breeding for yield.